2018
DOI: 10.1002/hyp.11444
|View full text |Cite
|
Sign up to set email alerts
|

Understanding land use and cover change impacts on run‐off and sediment load at flood events on the Loess Plateau, China

Abstract: The Loess Plateau has been experiencing large‐scale land use and cover changes (LUCCs) over the past 50 years. It is well known about the significant decreasing trend of annual streamflow and sediment load in the catchments in this area. However, how surface run‐off and sediment load behaved in response to LUCC at flood events remained a research question. We investigated 371 flood events from 1963 to 2011 in a typical medium‐sized catchment within the Plateau in order to understand how LUCC affected the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 56 publications
(135 reference statements)
2
23
0
1
Order By: Relevance
“…Hümann et al (2011) in the forest land of Southwest Germany found that forest land contributes to reducing the floods as runoff was higher in the agricultural land. Similar findings in the Loess Plateau in China were measured by Zhang et al (2018) who analyzed 371 flood events and demonstrated that floods accounted for 49.6% to 91.8% of their mean annual totals of runoff. The reduction of surface runoff and associated sediment yield in floods explained about 85.0% to 89.2% of the sediment yield.…”
Section: Introductionsupporting
confidence: 82%
“…Hümann et al (2011) in the forest land of Southwest Germany found that forest land contributes to reducing the floods as runoff was higher in the agricultural land. Similar findings in the Loess Plateau in China were measured by Zhang et al (2018) who analyzed 371 flood events and demonstrated that floods accounted for 49.6% to 91.8% of their mean annual totals of runoff. The reduction of surface runoff and associated sediment yield in floods explained about 85.0% to 89.2% of the sediment yield.…”
Section: Introductionsupporting
confidence: 82%
“…在全球气候变化背景下, 由于自然过程和人类 活动的共同作用, 全球许多河流的径流输沙发生了 很大的变化 [1,2] 。Li 等 [2] 研究表明, 全球大河 24%径 流量发生了显著变化, 40%输沙量发生显著变化, 其 中亚洲大河输沙量大部分呈现显著下降趋势, 亚马 逊河含沙量呈现上升趋势。不仅河流的径流和输 沙过程已被明显改变, 已有研究发现 [3] [4] 、 煤炭 开采对水循环的影响 [5,6] 、 流域水文特性 [7,8] 等进行了 一定研究。Sun 等 [9] [12] : 当样本趋势显著时, 常采用倾斜度β [15] 表示系 显著突变点。Lee-Heghinian 法 [17] 主要基于贝叶斯 [19] 分别为: [21] , 导致流域产水产沙减少; 其次, 国 家开始实施大规模退耕还林还草和天然林禁伐等 人工生态修复工程, 造成水沙的进一步减少 [22] , 截至…”
Section: 引言unclassified
“…Recent research has shown that the vegetation cover has greatly improved since 1999 (Zhang et al, 2018). Since then, there have been a lot of studies on soil erosion and vegetation over the Loess Plateau.…”
Section: The Case Study Area China's Loess Plateaumentioning
confidence: 99%